Involvement of Small Colony Variant-Related Heme Biosynthesis Genes in Staphylococcus aureus Persister Formation in vitro - Wang, Xuyang; Li, Weizheng; Wang, Wenjie; Wang, Shiyong; Xu, Tao; Chen, Jiazhen; Zhang, Wenhong (Frontiers in Microbiology, 2021)
Background: Persisters are important reasons for persistent infections, and they can lead to antibiotic treatment failure in patients and consequently chronic infection. Staphylococcus aureus small colony variants (SCVs) have been shown to be related to persistent infection. Mutations in the genes of the heme biosynthesis pathway lead to the formation of SCVs. However, the relationship between heme production genes and persister has not been tested. Methods:HemA and hemB were knocked out by allelic replacement from S. aureus strain USA500 separately, and then, the heme deficiency was complemented by overexpression of related genes and the addition of hemin. The stress-related persister assay was conducted. RNA-sequencing was performed to find genes and pathways involved in heme-related persister formation, and relative genes and operons were further knocked out and overexpressed to confirm their role in each process. Results: We found that heme biosynthesis deficiency can lead to decreased persister. After complementing the corresponding genes or hemin, the persister levels could be restored. RNA-seq on knockout strains showed that various metabolic pathways were influenced, such as energy metabolism, amino acid metabolism, carbohydrate metabolism, and membrane transport. Overexpression of epiF and operon asp23 could restore USA500∆hemA persister formation under acid stress. Knocking out operon arc in USA500∆hemA could further reduce USA500∆hemA persister formation under acid and oxidative stress. Conclusion: Heme synthesis has a role in S. aureus persister formation.